Effect of E-Wom on Social Media and Brand Image on Decisions Society Saving in Sharia Bank Connection - Saleh, Idris; Ritonga, Julpahmi; Harahap, Amhar Maulana; Hasibuan, Laila Kalsum; Lubis, Fatimah Sakdiah (Journal of Islamic Financial Technology, 2023)
The purpose of this study was to determine the effect of E-WOM and brand image on people's decisions to save in Islamic banks. The type of research used is quantitative research with primary data sources and secondary data. The sampling technique was determined by probability sampling data with a total sample of 88 people. Data processing uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, t test (partial) and F test (simultaneous) and test the coefficient of determination R2.In this study, E-WOM partially has a significant effect on people's decision to save at Panyabung Sharia Bank with a significant level value of 0.466 0.05 and Brand Image partially has a significant effect on people's decision to save at Panyabung Sharia Bank with a significance level value of 0.432 0 ,05. Whereas simultaneously E-WOM and brand image affect people's saving decisions at Panyabungan Islamic Bank, namely Fcount 110.306 Ftable 3.10, the results of this study indicate that E-WOM and brand image have a distribution of saving decisions of 72.2%. , while 27.8% is influenced by other variables not examined in this study.Keywords: E-WOM (Electronic Word Of Mouth), Brand Image, Saving Decision